2014
DOI: 10.5935/0004-2749.20140083
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral acute visual loss from Rathke’s cleft cyst apoplexy in a patient with dengue fever

Abstract: Hemorrhagic complications of optic pathway diseases are extremely rare causes of acute visual loss associated with dengue fever. In this paper we report a patient presenting with dengue fever and bilateral acute visual loss caused by chiasmal compression due to Rathke's cleft cyst apoplexy. Considering the importance of early diagnosis and treatment to visual recovery, apoplexy of sellar and suprasellar tumors should be considered in the differential diagnosis of patients with acute visual loss and dengue feve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Dear Editor, The recent report on "dengue and chiasmal compression" is very interesting (1) . Suzuki et al reported a case "presenting with dengue fever and bilateral acute visual loss caused by chiasmal compression due to Rathke's cleft cyst apoplexy" and concluded that "apoplexy of sellar and suprasellar tumors should be considered in the differential diagnosis of patients with acute visual loss and dengue fever (1) ".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, The recent report on "dengue and chiasmal compression" is very interesting (1) . Suzuki et al reported a case "presenting with dengue fever and bilateral acute visual loss caused by chiasmal compression due to Rathke's cleft cyst apoplexy" and concluded that "apoplexy of sellar and suprasellar tumors should be considered in the differential diagnosis of patients with acute visual loss and dengue fever (1) ".…”
mentioning
confidence: 99%
“…Suzuki et al reported a case "presenting with dengue fever and bilateral acute visual loss caused by chiasmal compression due to Rathke's cleft cyst apoplexy" and concluded that "apoplexy of sellar and suprasellar tumors should be considered in the differential diagnosis of patients with acute visual loss and dengue fever (1) ". The hemorrhagic complications of severe dengue infection are not uncommon and may present with ophthalmological symptoms.…”
mentioning
confidence: 99%
“…Esse tipo de lesão é descrito como achado em autópsias em até 22% de pacientes sem histórico de disfunção hiposifária (40,41) . Raramente, esses cistos podem crescer progressivamente e comprimir estruturas adjacentes como o quiasma óptico ou ainda sangrar (42) , causando sintomas visuais, cefaleia e alterações hormonais agudas. A confirmação diagnóstica é histopatológica.…”
Section: Epidemiologiaunclassified